2008
DOI: 10.1029/2007ja012958
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of coronal type III solar radio bursts: 2. Dynamic spectrum for typical parameters

Abstract: [1] Predictions are presented for the dynamic spectrum of a coronal type III burst observed at Earth, using a newly developed simulation model and employing realistic electron release and coronal parameters. The spectrum is studied in detail in association with the dynamics of beam and waves in the source. The frequency drift rate, radio flux, brightness temperature, and temporal profile of the type III burst agree semiquantitatively with typical observations. The simulation model is thus viable. Because of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
28
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 43 publications
12
28
0
1
Order By: Relevance
“…We see from Figures a and b that both bursts are weak yet are observable for typical instruments with thresholds ≈1 sfu (solar flux unit) (=10 −22 Wm −2 Hz −1 ). This result of weak f p emission is consistent with our previous simulations that have Maxwellian spectra for the injected electrons [e.g., Li et al , , ]. Figures a and b show that at a given f , the burst in S1 has a much earlier onset and slightly earlier termination than in S2.…”
Section: Representative Simulationssupporting
confidence: 90%
“…We see from Figures a and b that both bursts are weak yet are observable for typical instruments with thresholds ≈1 sfu (solar flux unit) (=10 −22 Wm −2 Hz −1 ). This result of weak f p emission is consistent with our previous simulations that have Maxwellian spectra for the injected electrons [e.g., Li et al , , ]. Figures a and b show that at a given f , the burst in S1 has a much earlier onset and slightly earlier termination than in S2.…”
Section: Representative Simulationssupporting
confidence: 90%
“…The values of v b in Figure 3f are quantitatively consistent with the beam speeds V obtained directly from the simulated electron distribution function f e [ Li et al , 2008b]. Here v b characterizes the region in phase space where f e is unstable (∂ f e /∂ V > 0).…”
Section: Effects Of Varying Coronal Conditionssupporting
confidence: 79%
“…The model is based on quasilinear electron‐Langmuir wave equations augmented with nonlinear terms for Langmuir electrostatic (ES) decay, and with nonlinear wave‐wave processes that produce electromagnetic (EM) waves at f p and 2 f p . In the second paper (paper 2) [ Li et al , 2008b] we presented the simulation results for a coronal type III burst observed at Earth using a set of realistic parameters for the beam acceleration and coronal conditions. Our detailed comparisons between the simulations and typical observations showed quantitative or semiquantitative agreement in the spectral characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In this work for a first time we are concerned with the investigation of the generation of Langmuir waves, its spectra and total energy density, and also the gas-dynamical parameters of the beam such as the height of the plateau in the beam distribution function, its upper velocity boundary, the beam width in velocity space, and its local and average velocity of propagation in the solar wind plasma by considering a Lorentzian background distribution function. Gas-dynamical parameters are helpful in understanding the dynamic spectra of type III radio bursts (Li et al 2008a(Li et al , 2008b.…”
Section: Introductionmentioning
confidence: 99%